Transmutation Methodology + Neural Networks: A Philological and Didactic Project - Golev Nikolay (Виртуальная коммуникация и социальные сети)
The transmutation approach can be combined with artificial intelligence (AI) programs to develop speech skills in schoolchildren and university students of philology or pedagogical majors. The article introduces the linguadidactic project of Transmutation Methodology + Neural Networks. AI programs provide a wide range of inter-code transformations of a verbal text, e.g., it can be encoded as music, drama, visual art, dance, animation, photo, video, etc. R. O. Jacobson called them transmutations, i.e., transformations of verbal signs into signs of non-verbal systems. Transmutations activate both the left and the right hemispheres, the latter being responsible for sensory perception and interpretation of a verbal literary text. This phenomenon opens up huge prospects for philological didactics. During transmutation activities, students implement verbal images and ideas processed with AI programs. By automatizing a complex creative process, students penetrate into the meaning of the original text, e.g., by structuring and restructuring it, actualizing its most significant or attractive elements, etc. By becoming authors, students assume an active speech position as they formulate the promt for the AI program, i.e., a description (model, structure) of the original text. The functional unity of the transmutation approach and AI programs demonstrate good prospects for linguistic didactics.